The Resistive Switching Characteristics and Electrical Conduction Mechanisms of Memory Devices Based on Nanocomposite - Kim Ngoc, Pham; Tu Uyen, Doan Thi; Nhu Phuong, Pham Le Quynh; Xuan Dat, Mai Ngoc (VNU Journal of Science: Mathematics - Physics, 2021)
The resistive switching memory device based on nanocomposites has become a potential candidate in the data storage field. Understanding resistive switching characteristics and electrical conduction mechanisms may support the appropriate way to fabricate and control the operation of a device. In this study, a capacitor-like structure using PVA-ZnO as an insulator layer was fabricated by a solution method. The crystalline structure, morphology, and absorption spectrum of ZnO nanoparticles were revealed respectively. The resistive switching effect was observed with the ON/OFF ratio of 0.5´10 2 , high endurance, excellent retention and the electrical transport mechanisms were followed by the SCLC and Ohmic’s law in the low resistance state and Flower- Nordheim tunneling in the high resistance state. The resistive switching mechanism was contributed by the oxygen vacancies in ZnO nanoparticles and the oxygen ions in the bottom electrode.